2021
DOI: 10.1108/acmm-04-2021-2472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu addition to low-alloy structural steel on the resistance against corrosion by the Pseudomonas aeruginosa biofilm

Abstract: Purpose Low-alloy structural steels (LASS) face severe microbiologically influenced corrosion (MIC) in their service environments. To mitigate this issue, Cu is often used as an alloying element owing to its intrinsic antimicrobial activity. However, the antibacterial performance and biofilm resistance of Cu-containing LASS (Cu-LASS) are still unclear. This study aims to analyze the effect of Cu addition to 420 MP LASS on its MIC by the Pseudomonas aeruginosa biofilm. Design/methodology/approach Scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…More and more attention has been paid to the research of anticorrosion technologies such as fungicides, enhancers, antibacterial stainless steel and antibacterial coatings (Koch et al, 2001), while the chemicals involved in these treatment methods are basically toxic and harmful, without good environmental characteristics, and short service life is an inevitable problem. These chemicals will continue to be released into the environment, resulting in toxicity, carcinogenicity, environmental pollution, increased bacterial resistance (Zhuk et al, 2014) and bioaccumulation (Bhat et al, 2011;Li et al, 2021a). "Bacteriostasis with bacteria" is the use of beneficial microorganisms to inhibit the corrosion of harmful microorganisms (Wang et al, 2023b) and achieves the purpose of inhibiting MIC through competitive growth, metabolite action, microenvironment control and modification.…”
Section: Introductionmentioning
confidence: 99%
“…More and more attention has been paid to the research of anticorrosion technologies such as fungicides, enhancers, antibacterial stainless steel and antibacterial coatings (Koch et al, 2001), while the chemicals involved in these treatment methods are basically toxic and harmful, without good environmental characteristics, and short service life is an inevitable problem. These chemicals will continue to be released into the environment, resulting in toxicity, carcinogenicity, environmental pollution, increased bacterial resistance (Zhuk et al, 2014) and bioaccumulation (Bhat et al, 2011;Li et al, 2021a). "Bacteriostasis with bacteria" is the use of beneficial microorganisms to inhibit the corrosion of harmful microorganisms (Wang et al, 2023b) and achieves the purpose of inhibiting MIC through competitive growth, metabolite action, microenvironment control and modification.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al (2023) have reported that adding Cr in steel also promotes the formation of an inner electronegative film to repel Cl − ions. Li et al (2021) have found that Cr is more likely to repair defects in the rust layer via a degree of elemental bias. Liu et al (2016) have reported that although no Cr oxides are found in the rust layer, Cr enhances the formation of uniform amorphous ferric oxyhydroxide, which exhibits a better protection against corrosion.…”
Section: Introductionmentioning
confidence: 99%